Development of Discrete Trial Training (DTT) Procedure in Smart Applied Behavior Analysis (Smart ABA) for Autism - Anwar, Arneliza; Sutadi, Rudy; Miranda, Chairita (Journal of Psychology and Behavior Studies, 2022)
Lovaas was the first professional to use the principle of behavior modification for autism with a technique he called DTT (Discrete Trial Training), which later to be known as ABA (Applied Behavior Analysis). Through his study, Lovaas found that 47% of subjects had excellent results. While 42% with varying degrees, and the other 11% of subjects very little progress. In DTT, there are 2 possible responses, but the researchers' observations do not seem to be just 2 possibilities. This study's goal is to improve discrete trial training (DTT) procedures to increase the effectiveness of Smart Applied Behavior Analysis therapy for autism spectrum disorder. This study uses quantitative methods with a literature review research design. Research data is obtained through interviews, document studies, and literature reviews (journals and websites). The study focused on the researchers' findings that were adapted to earlier theories. The study was conducted at the researchers' autism clinic. During the implementation of therapy using DTT, the researchers observed that the child's response is not only 2, namely correct and incorrect. Based on the study conducted, it was obtained that there were 5 possible responses: Correct, incorrect, partial-correct, off-task, and no-response. Each of which required different feedback and its subsequent sequences, as well as the possibility of different causative factors which require different interventions. Further research with large and multi-center samples will further increase the effectiveness of DTT applications in Smart ABA for autism. This study was based on the researchers' findings while observing, mentoring, and supervising autism therapists.